Dose of Incorporated Immunodominant Antigen in Recombinant BCG Impacts Modestly on Th1 Immune Response and Protective Efficiency against Mycobacterium tuberculosis in Mice - Hui Ma; Kang Wu; Fang Liu; Hua Yang; Han Kang; Ning-Ning Chen; Qin Yuan; Wen-Jiang Zhou; Xiao-Yong Fan (Journal of Immunology Research)
One approach for improving BCG efficacy is to utilize BCG as vehicle to develop recombinant BCG (rBCG) strains overexpressing Mycobacterium tuberculosis (M. tb) antigens. Also expression level of a candidate antigen should impact the final T cell responses conferred by rBCG. In this study, based on our previously constructed differential expression system, we developed two rBCG strains overexpressing M. tb chimeric antigen Ag856A2 (coding a recombinant ag85a with 2 copies of esat-6 inserted at Acc I site of ag85a) at differential levels under the control of the subtly modified furA promoters. These two rBCG strains were used to vaccinate C57BL/6 mice and exploit dose of incorporated antigen in rBCG to optimize immune response and protective efficiency against M. tb challenge in mouse model. The results showed that rBCG strains overexpressing Ag856A2 at differential levels induced different antigen-specific IFN-γ production and comparable number of M. tb-specific CD4 T cells expressing IL-2. M. tb challenge experiment showed that rBCG strains afforded enhanced but comparable immune protection characterized by reduced bacillary load, lung pathology, and inflammation. These results suggested that the dose of antigens incorporated in rBCG can impact T cell immune responses but imposed no significantly differential protective efficacies.